Academic Procrastination of High School Students During the Covid-19 Pandemic: Review from Self-Regulated Learning and the Intensity of Social Media - Eva Latipah; Hanif Cahyo Adi; Farah Dina Insani (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
The Covid-19 pandemic has an impact on increasing procrastination of study assignments (academic procrastination) in Islamic Religious Education in Senior High Schools. This occurs because students have low self-regulated learning (SRL), and on the other hand, have high social media intensity. This study aims to examine the relationship between SRL and the intensity of social media with academic procrastination. This research is quantitative using the SRL scale, academic procrastination scale, and social media intensity questionnaire for data collection. The sample was determined using the Slovin formula in order to obtain a sample of 118 students. The data analysis technique used regression analysis. The results showed: 1) There was a significant negative relationship between self-regulated learning and academic procrastination with a value of r = -4.125 and a value of p = 0.00 (p <0.05). 2) There is a significant positive relationship between the intensity of social media and academic procrastination with r=5.111 and p=0.00 (p<0.05). 3) There is a significant positive relationship between self-regulated learning and the intensity of social media simultaneously with academic procrastination with a value of F=15.106 and a value of p=0.00 (p<0.05). 4) The effective contribution (R2) of the two variables is 30.5%. Thus, self-regulated learning and the intensity of social media can be predictors of PAI's academic procrastination.